Consumer preference and willingness to pay for low-residue vegetables: Evidence from discrete choice experiments in China - Wang, Jian; Zhou, Liangru; Ni, Zhilong; Wu, Wenhao; Liu, Guoxiang; Fu, Wenqi; Zhang, Xin; Tian, Jing (Frontiers in Sustainable Food Systems, 2022)
Introduction This study aims to investigate consumers' cognition, preference and willingness to pay (WTP) for celery with low pesticide residues, and to provide evidence from a consumer perspective for government food safety regulation. Method A survey was conducted on the population over the age of 18 in 6 provinces of Shanghai, Guangdong, Sichuan, Hunan, Hebei and Heilongjiang in China, in order to improve the representativeness of sample. The study carried out a survey of respondents' cognitive attitudes towards low-residue vegetables, and applied a discrete choice model (DCE) to simulate different scenarios of consumers buying vegetables. The DCE included residue level, appearance, taste, and price and finally constructed 24 choice sets. Respondents' preference for low-residue celery and WTP were analyzed using a mixed logit model. Result A total of 1292 respondents were surveyed. The model results showed that consumers had the highest positive preference for pesticide-free celery. For the Chinese consumers, price was the most important attribute, followed by the residue level, taste, and appearance. Consumer WTP for pesticide-free celery was11.17CNY/500g. Factors affecting consumer preferences were age, gender, income, education, whether they had children, or paid attention to pesticide residue in vegetables, and related reports of pesticide residue exceed the standard in vegetables. Conclusion Our study is more finely divided at the residue level, and the findings provide useful information for producers and policy makers.